Spiritualisasi Nilai-Nilai Islam Dalam Pembelajaran Tematik Di Tingkat Madrasah Ibtidaiyyah - Ulfa Futri Hasyimiyyah Qissa ‘Ali (STAI Siliwangi Bandung, 2017)
Thematic learning seeks to harmonize science comprehensively, while Islamic education seeks to develop the divine potential with features: muttaqin, mu'minin, and muhsinin. If the values ​​of Islam can be integrated kaffah in thematic learning then the objectives of thematic learning will be achieved in full. With the implementation of the integration of Islam through thematic learning, there will be spiritualization (a change in students by incorporating the values ​​of faith and piety, as the stock of students, especially students of Madrasah Ibtidaiyah to be ready to face the challenges in the future.This study uses Quantitative Descriptive Approach. Descriptive method is a method intended to describe or describe the phenomena that exist, whether natural phenomena or human engineering that examines the shape, activity, characteristics, changes, relationships, similarities and differences with other phenomena. The data were collected using observation.